Effect of biosolids application and role of dissolved organic matter on the movement of heavy metal in soils - Al-Wabel, Mohammad I., author; Westfall, Dwayne G., advisor; Heil, Dean, advisor; Barbarick, K. A., committee member; Stednick, John D., committee member (Colorado State University. Libraries, 2001)
The use of biosolids as a soil fertilizer has been shown to be an agronomically beneficial practice. Biosolids supply nutrients and organic matter to semi-arid soils. However, biosolids contain heavy metals. Long-term use may result in the accumulation of heavy metals in soils. The movement of heavy metals in the soil profile is an important environmental concern and not well understood by scientists This research was conducted on two soils that received long-term biosolids application from different biosolid sources. One was a dryland soil (Fine, smectitic, mesic Aridic Argiustoll) that had received semi-annual application from 1982 to 1992, and another was an irrigated soil (Loamy, mixed, mesic Arenic Ustollic Haplargid) that had received six applications from 1988 to 1997. Two different sources of biosolids were applied at a rate of 26.8 and 28 Mg ha-1 yr-1, respectively. Soil profiles were collected from these two locations to depth of 100-cm. Electrical conductivity (EC), pH, organic matter (O.M.) and NO3-N, total and AB-DTPA extractable Cu, Zn, and Pb contents of the samples were measured. A column study was also conducted to determine the effect of dissolved organic carbon (DOC) and EC of the leaching water on the movement of heavy metals through the soil profile. The results for the dryland soil profile indicated that the concentration of Cu, Zn and Pb increased in the topsoil and that Zn and Cu moved below the treated layer while Pb did not. Also, we found a positive correlation between O.M. and Cu, Zn and Pb, while their correlation was negative with EC and pH. In the irrigated soil, the treated and untreated soils were found to be originally different. This made the determination of the effect of biosolids addition on soil properties difficult. The results of the column study did show that DOC was significantly increased immediately after the addition of biosolids and had decreased to near background levels after ten leaching cycles. The addition also increased both DOC and Cu in the column effluents resulting in a positive correlation between Cu and DOC across application treatments for both soils. Zn mobility was positively correlated with EC. From the anodic stripping voltammetry (ASV) analysis, the results showed that more than 99% of Cu and Zn and at least 90% of Pb complexed with either DOC or mineral colloids and only a very small percentage of the total dissolved metals concentrations existed as free ions or inorganic complexes. Moreover the results also showed the highest concentration of the DOC and the heavy metals in the leaching effluent were observed immediately after biosolids addition.
Keywords: soil sciences